Impact of export determinants on the export sector in Republic of Serbia - Perić, Milica; Filipović, Sanja (Industrija, 2018)
In order to show the effect of export determinants on the export in the Republic of Serbia, this research comes to examine the correlation between export determinants and the degree of impact of export determinants on export in Republic of Serbia in the period of 2005-2016. This study applies the SPSS 23 software by Correlation matrix using Pearson coefficient in order to show the connection between export determinants and export, as well as the Linear Regression Models, in order to show the degree of impact of the export determinants on export. The analysis revealed the existence of the significant correlation between export and several hypothetical export determinants – import, GDP, GDP per capita, savings, population, employment, productivity of work, exchange rate, and consumption prices – as well as the impact of those on export. It stresses as well that there is no relationship between export and FDI, investments, and industrial production.